PENDIDIKAN POLITIK BAGI PEMILIH PEMULA PERHIMPUNAN MAHASIWA KATOLIK REPUBLIK INDONESIA (PMKRI) CABANG KOTA SAMARINDA PADA PEMILU 2024 - Ahmad Yani; Trisna Waty Riza Eryani; Gregorius Agung Salmon; Muhammad Wendy (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The Indonesian people will hold a General Election (PEMILU) in 2024, which is a routine agenda held every five years. A quality Democratic Party, in this case the Election, will be able to give birth to new national leaders. From quality national leaders, they will be able to produce good strategies and policies, achieving better quality progress, especially in improving people's welfare. First-time voters are those who have not been able to exercise their voting rights in the previous five-year Election, namely the 2019 Simultaneous Election, so they cannot exercise their voting rights because they are not yet categorized as voters. This community service theme is Political Education for First-time Voters of the Indonesian Christian Student Association (PMKRI) Samarinda City Branch in the 2024 Election. The purpose of this service is to provide understanding to first-time voter participants who are members of the Samarinda City Student Association organization to actively participate in the election process and utilize their voting rights properly. Based on the results of the service, it can be concluded that this integrated scheme community service activity is able to increase the understanding of first-time voters about elections, political education, and willingness to participate in politics, so they can channel their aspirations according to their conscience.